Finding the right management approach in independent hotels. Issue 7 (3rd June 2019) - Nazarian, Alireza; Atkinson, Peter; Foroudi, Pantea; Dennis, Karen
Abstract : Purpose: This study aims to identify factors that managers can influence to improve effectiveness by examining the relationship between leadership and effectiveness in small and medium-sized independent hotels. Design/methodology/approach: In total, 272 valid questionnaires were collected from managers of 83 small and medium-sized independent hotels in the Netherlands by using selective and snowball sampling techniques. A two-stage structural equation modelling approach was used to test the hypotheses. Findings: Surprisingly, in contradiction to previous studies, neither transactional nor transformational leadership had a direct effect on organisational effectiveness. Instead, the effect was through the intervening variables of ability to acquire resources and reward mechanisms. Research limitations/implications: The contradiction between this and previous studies may be due to the fact that constructs used in this study do not have the universal applicability that is customarily assumed and further investigation is needed. Practical implications: This study suggests that managers in this type of hotel, first, should be adaptable in their leadership style and not rely on transactional leadership alone; second, managers must pay attention to resource acquisition; and third, managers must retain staff by using the right reward mechanism. Originality/value: This study contributes to the literature of leadership and effectiveness in small and medium-sized independent hotels by being the first to focus on the impact of ability to acquire resources and reward mechanism. It also makes an important contribution to the growing body of hospitality literature that probes the supposed universal validity of organisational studies' constructs.